Insurance and Individual Incentives in Adaptive Contexts - Viscusi, W. Kip (Econometrica, 1979)
Opportunities for individual learning in multi-period insurance contexts introduce fundamental economic aspects not present in conventional static models. Using a twoperiod model in which there are two states (accident and no accident), it is shown that more precise prior probability assessments lead to increased insurance coverage and reduced self-protection. These dynamic adverse incentive problems can be diminished by merit rating, which has a backwards influence on earlier actions. Self-protection and insurance purchases in the initial period respond in opposite fashion to changes in insurance prices in the second period, the interest rate, and parameters of the prior probability assessment.